(untitled) (Research, Society and Development, 2020)
This research aims to analyze the levelized level energy cost of energy (LCOE) of wind farms with tethered airfoils. For this, it was considering the technical characteristics of the system, the location of operation, the necessary investments and the characteristics of the Brazilian market, to analyze the levelized cost of energy of three wind farm scenarios: Classic wind farm, Wind farm with tethered airfoils operating in Pumping Kite mode and a hybrid park with the two park configurations studied. The research makes use of the LCOE method. The results indicate that the technology with wired airfoils requires less investment and that wind farms with this technology can generate more energy than a classic wind farm of the same nominal power, since the wired airfoils can exploit high altitude winds, where they are more frequent and strong. The results also indicate that wind farms with wired airfoils are not only economically viable, but produce energy at a level cost, well below the values currently practiced for the sale of energy in the domestic market.